Milk thistle seed cold press oil attenuates markers of the metabolic syndrome in a mouse model of dietary‐induced obesity. Issue 12 (12th October 2020) - Shen, Hsin‐Hsueh; Alex, Ragin; Bellner, Lars; Raffaele, Marco; Licari, Maria; Vanella, Luca; Stec, David E.; Abraham, Nader G.
Abstract: Milk thistle cold press oil (MTO) is an herbal remedy derived from Silybum marianum which contains a low level of silymarin and mixture of polyphenols and flavonoids. The effect of MTO on the cardiovascular and metabolic complications of obesity was studied in mice that were fed a high‐fat diet (HFD) for 20 weeks and treated with MTO for the final 8 weeks of the diet. MTO treatment attenuated HFD‐induced obesity, fasting hyperglycemia, hypertension, and induced markers of mitochondrial fusion and browning of white adipose. Markers of inflammation were also attenuated in both adipose and the liver of MTO‐treated mice. In addition, MTO resulted in the improvement of liver fibrosis. These results demonstrate that MTO has beneficial actions to attenuate dietary obesity‐induced weight gain, hyperglycemia, hypertension, inflammation, and suggest that MTO supplementation may prove beneficial to patients exhibiting symptoms of metabolic syndrome. Practical applications: Natural supplements are increasingly being considered as potential therapies for many chronic cardiovascular and metabolic diseases. Milk thistle cold press oil (MTO) is derived from Silybum marianum which is used as a dietary supplement in different parts of the world. The results of the present study demonstrate that MTO supplementation normalizes several metabolic and cardiovascular complications arising from dietary‐induced obesity. MTO supplementation also had anti‐inflammatory actions in the adipose as well as the liver. These results suggest that supplementation of MTO into the diet of obese individuals may afford protection against the worsening of cardiovascular and metabolic disease and improve inflammation and liver fibrosis. Abstract : Schematic presentation of postulated mechanisms by which cold pressed milk thistle oil intake to obese mice lead to marked suppression of inflammatory markers including NOV and TWIST and diminished liver fibrosis markers including MMP2 and MMP9. Additionally, cold press MTO reverses these changes, obesity suppress effect, and thermogenic genes such as (UCP1, PRMD16), mitochondrial respiration as displayed by the increase in oxygen consumption and improving insulin receptor phosphorylation. Hence, intake cold press MTO offers a multifunctional clinical approach for the treatment of Metabolic Syndrome.